Effect of climate, growing region, country of origin, and post-harvest processing on the of content chlorogenic acids (CGAs) and aromatic compounds in roasted coffee beans - Robert Rusinek; Bohdan Dobrzański; Marzena Gawrysiak-Witulska; Aleksander Siger; Anna Oniszczuk; Sylwester Tabor; Marek Gancarz (Scientific Reports)
Abstract The paper presents an analysis of the content of caffeine, tocopherols, and phenolic compounds as well as the volatile compound profile and volatile compound emission intensity in relation to the cultivation parameters of the Typica variety of Arabica coffee from Peru, Costa Rica, Guatemala, and Ethiopia. The study provides a detailed description of the cultivation and post-harvest parameters of the coffee types selected for the analyses. Special emphasis was placed on the analysis of the plantation altitude effect on instrumentally determined aromatic parameters and bioactive properties. The analyses were performed with the use of high-performance liquid chromatography, gas chromatography, and an electronic nose. The investigation results indicate a significant effect of the altitude of coffee cultivation on the most important biological and chemical properties of coffee beans, e.g. caffeine content, phenolic content, intensity of volatile compound emission, and coffee aroma. Other factors, such as shading and post-harvest processing, were also found to interact with the cultivation altitude and influence the content of these coffee attributes.